2022 Peggi Guenter Excellence in Clinical Practice Lectureship: Expanding the clinical practice of nutrition—Challenging the known, exposing inconvenient truths, and engaging the young. (8th November 2022) - McClave, Stephen A.
Abstract: To expand the clinical practice of nutrition, the influence of the American Society for Parenteral and Enteral Nutrition (ASPEN) must reach an audience outside the nutrition community, must be relevant and meaningful to clinicians, and must meet the needs of specific patient populations throughout medical and surgical specialties. Individual members of our society need to share their enthusiasm and expertise with youth through conscious, intentional mentorship. Efforts should be made to promote advanced practice, increasing the skill set of the individual nutritionist. Nutrition research should be of the highest quality, matching that of any current medical or surgical discipline. Members of a nutrition consult service should speak the same language as the physicians they work with, through discussions on rounds and in communication through their charting and consult notes. Our societal guidelines should define clinical practice. Relationships with other societies should be cultivated through these guidelines, position papers, and public health initiatives to increase the relevance and impact of our society. To position itself for future generations, the role of ASPEN should be expanded to be more comprehensive and involve all nutrition aspects of patient care.